The reader / 1. - Chee, Traci (Chee, Traci. Sea of ink and gold, 2016)
"Set in a world where reading is unheard-of, Sefia makes use of a mysterious object to track down who kidnapped her aunt Nin and what really happened the night her father was murdered"--Provided by publisher.